Comparison between MAT flow fixed bed and batch fluidized bed reactors in the evaluation of FCC catalysts. 2. Naphtha composition - Passamonti, Francisco Javier (2009)
A comparison was performed between the performances of a MAT type reactor(flow fixed bed) and a CREC riser simulator reactor(batch fluidized bed) in the conversion of two VGO feedstocks(aromatic and paraffinic types) over three commercial equilibrium FCC catalysts, under similar conditions. In both units the reaction temperatures were 500 and 550 °C. The catalyst-to-oil relationships were from 2.3 to 6.2(cumulative) and 6.2, and the times were from 15 to 40 s(time on stream) and from 5 to 30 s(reaction time) in the MAT reactor and the CREC riser simulator reactor, respectively. Results were compared in terms of the composition of the naphtha, in view of its contribution to the gasoline pool. Advantages were observed with data from the CREC riser simulator reactor, mainly derived from the fact that naphtha yields were, in general, closer to commercial values and showed a stable primary product behavior. Thus, they are easier to analyze as naphtha selectivities did not depend on the conversion reached. On the contrary, naphtha yields in the MAT reactor showed a maximum as a function of conversion. The comparison of the product distributions observed in the naphthas from each unit at the same conversion level showed that they can be very different; the naphtha obtained in the CREC riser simulator reactor was more paraffinic and less aromatic than the one obtained with the MAT reactor, and the proportions were similar to commercial values. Ranks of catalysts based on the various hydrocarbon fractions observed in the naphtha from each setup also differed in most of the cases. The differences in the results could be the consequence of notoriously different contact between reactants and catalyst and operative modes in each reactor, then impacting on the complex set of reactions occurring in FCC.